Stance and politeness in spoken Latvian - Chojnicka, Joanna (Lingua Posnaniensis, 2015)
The present article is concerned with the concept of stance and its relationship to face, face work and politeness applied to Latvian spoken discourse. It offers an extensive review of relevant literature on stance and politeness theories, followed by an illustrative analysis of politeness strategies and stance markers found in a radio interview. On this basis, the article argues that stance markers - epistemic, evidential, mirative and hedging devices - may be considered a negative politeness strategy, responding to the speaker’s and hearer’s desire for autonomy. In conclusion, it suggests a hypothesis that could explain differing use of stance markers and politeness strategies by speakers fulfilling varying conversational roles and of various social standing.